Categorical data analysis using the SAS system - Stokes, Maura Ellen (SAS Institute, 2000)
Discusses hypothesis testing strategies for the assessment of association in contingency tables and sets of contingency tables. Also discusses various modeling strategies available for describing the nature of the association between a categorical outcome measure and a set of explanatory variables.